Microsporogenesis is simultaneous in the early-divergent grass Streptochaeta, but successive in the closest grass relative, Ecdeiocolea - Sajo, Maria Das Gracas [UNESP]; Furness, Carol A.; Rudall, Paula J. (Taylor & Francis As, 2009)
Simultaneous microsporogenesis is described for the first time in a grass, Streptochaeta spicata Schrad., a tropical Brazilian species that belongs in the early-divergent subfamily Anomochlooideae. Microsporogenesis is successive in all other Poaceae examined so far, and most other members of the order Poales, to which grasses belong. The only other reports of simultaneous microsporogenesis in Poales are in Rapateaceae and some members of the cyperid clade (Juncaceae, Cyperaceae, Prionium and Thurnia). Among the graminids, Ecdeiocolea (the putative closest relative to Poaceae) is successive, as are Joinvillea, Flagellaria and all other Poaceae, indicating that the simultaneous condition is autapomorphic in Streptochaeta, though Anomochloa has yet to be examined. Anther wall development in Streptochaeta is of the reduced type, as also in another early-divergent grass Pharus, though most other Poales, including most grasses, have the monocot type. In Streptochaeta, as in Pharus, the endothecium lacks thickenings, unlike other grasses that have a persistent endothecium with thickenings. The centrifixed anthers and nonplumose stigmas of Streptochaeta suggest entomophily.
Keywords: Ecdeiocolea; microsporogenesis; Poaceae; Poales; pollen development; Streptochaeta